Indian Literature in Southeast Asia - Francisco, Juan R. (Silliman Journal, 2024)
This article traces the influence of Indian literature in Southeast Asia. There are two levels at which this influence may be found: in art and religion, and in literature. In literature, the Indian influence is in the following forms: themes and motifs, direct borrowing of Sanskrit originals, and re-narration in Old Javanese, Old Malay and other local languages.